(untitled) (Delta Medical College Journal, 2015)
Background: : Slum dwellers are likely to be among the most deprived people in urban areas. Poor hygiene practices and inadequate sanitary conditions play major roles in the increased burden of communicable diseases within developing countries like ours. Objective: To assess the knowledge and practice about personal hygiene and environmental sanitation in selected slums of Dhaka city. Materials and method: This cross sectional study was conducted in purposively selected urban slum areas of Moghbazar slum, Bashabo slum and T&T slum of Dhaka city during February 2014 to April 2014. Convenient sampling technique was applied. Semi-structured pre-tested questionnaire was used and face to face interview was conducted. Total 475 subjects, irrespective of age and sex, were included in this study. Results: Out of 475 respondents, more than fifty percent slum dwellers resided in tin shaded room while 21.7% in kacha houses. Sixty six percent of the respondents used to drink water from tube-well and 24% used supplied water provided by the city corporation. The study revealed that near 59% of the respondents used sanitary latrine. About 67% slum dwellers regularly practiced hand washing before taking meal and 59.2% respondents used soap after defecation. About fifty percent respondents brushed their teeth regularly with tooth paste. Regarding personal cleanliness, 81% subjects took bath regularly while 78% washed clothes irregularly. A statistically significant relation was found between washing of hands before meal (p=0.001), washing of hands after defecation (p=0.02), tooth brushing (p=0.001), bathing (p=0.009), washing of cloths (p=0.001), use of footwear (p=0.63) with knowledge of personal hygiene of the slum dwellers. Conclusion: Continuous community hygiene education along with adequate access to water supply and sanitation improves hygiene behaviour and policy makers and health care providers should have definite strategy and implementation. Delta Med Col J. Jul 2015; 3(2): 68-73